MITOCHONDRIAL DNA VARIATIO OF THE RICE YELLOW STEM BORER, Scirpophaga incertulas, (LEPIDOPTERA: CRAMBIDAE) IN JAVA, INDONESIA - Hari Sutrisno (BRIN Publishing (Penerbit BRIN), 2015)
Scirpophaga incertulas is one of economically important rice pests in South East Asia, including Indonesia. Systematic investigation on biological characteristics of ecological races based on recently changed of agricultural practiced and environment has been conductedÂ in order to asses knowledge on genetic variation of population of S. incertulas in Indonesia. A 685 bp segment of mitochondrialDNA COII was amplified from 42 different yellow stem borer samples from five locations in Java. The objectives of this study were to generate mitochondrial CO II Â sequences for all available yellow stem borer Â samples and to define haplotypes and nucleotide sequence diversity of the different yellow stem borer populations. Six different haplotypes (YSB1, YSB2, YSB3, YSB4, YSB5 and YSB6) were identified in yellow stem borer populations. The majority of the sampled individuals caried haplotype YSB2. Overall, the results of Tajimaâ€™s test statistic indicated that the population of Java was D= 0.85201, which suggests that there was no indicative of purifying selection or there was no presence of deleterious mutation segregating in the population. However, the results were not significant (P> 0:10) and additional studies are required to confirm this finding.